Herodotus I 53 and its Transmission in Christian Greek Literature - Narro Sánchez, Ángel (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2013)
The Delphic oracle offers an answer to the Lydian king Croesus that will cause his attack against the Persians and his own defeat. This oracle appears as a dactylic hexameter in Aristotle’s Rhetoric for the fi rst time. Then, it will attract the attention of Christian apologists. However, its transmission will be altered by the term ποταμὸν, whose addition breaks the metrical scheme of the hexameter. Finally, we will be able to distinguish the sources used by the Byzantine authors who insert this oracle depending on whether they respect the hexameter following Aristotle or they insert the text following Eusebius. Thus, our study aims to analyze the transmission of this oracle from Herodotus’ History to Byzantine literature, with particular emphasis on Christian Greek literature, in which this second textual version will be consolidated.